A self-boosting microwave plasma strategy tuned by air pressure for the highly efficient and controllable surface modification of carbon. Issue 17 (8th March 2021) - Liu, Yanjing; He, Jiawei; Zhang, Bing; Zhu, Huacheng; Yang, Yang; Wu, Li; Zhang, Wencong; Zhou, Yanping; Huang, Kama
Abstract : Microwave enabled air plasma was boosted by a carbon fiber cloth (CFC) and used for the high-efficiency surface modification of the CFC, yielding CFCs with tunable contents of oxygen and each O-containing group. Abstract : Surface modification is required to improve the activity and compositing ability of carbonaceous materials for their application in numerous areas such as energy storage, aerospace applications, and construction reinforcement. However, current strategies are facing problems such as the involvement of expensive and corrosive chemicals, poor controllability, and breakage of the carbon skeleton, thus sacrificing the mechanical and electrical properties. In this study, a green and controllable self-boosting microwave technology is proposed for the high-efficient surface modification of carbon. Air was used as the only oxidant. A carbon fiber cloth (CFC) is exposed to microwave irradiation in air for 90 s, yielding CFC with a surface oxygen content of 25.73%, 54.41%, and 52.56% at 1 atm, 8000 Pa, and 80 Pa, respectively, as determined via X-ray photoelectron spectroscopy. Notably, the content of each oxygen-containing functional group ( e.g., –C–OH and –CO) is controllable by tuning the air pressure. Besides, CFC has enhanced mechanical and electrical properties. In comparison, CFC treated with a strong acid for 2 h only has a surface oxygen content of 21.4%, exhibiting greatly impaired electrical and mechanical properties. Numerical simulations at different pressures suggest that air plasma is triggered and boosted by the existence of CFC at 8000 Pa and 80 Pa, generating different electron number densities and electron temperature distributions, thus resulting in high-efficient and controllable modification.